2017
DOI: 10.1074/jbc.m115.712646
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin confers protection from acute colitis and restricts a B cell immune response

Abstract: Adiponectin demonstrates beneficial effects in various metabolic diseases, including diabetes, and in bowel cancer. Recent data also suggest a protective role in colitis. However, the precise molecular mechanisms by which adiponectin and its receptors modulate colitis and the nature of the adaptive immune response in murine models are yet to be elucidated. Adiponectin knock-out mice were orally administered dextran sulfate sodium for 7 days and were compared with wild-type mice. The severity of disease was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…Furthermore, leptin expression is elevated and adiponectin decreased in adipose tissue in rats with colitis fed with a normal diet, and this effect is markedly enhanced in rats fed with an HFD diet. This observation is further supported in studies in mice because the increased leptin and decreased adiponectin plasma levels and elevated expression of leptin and decreased adiponectin expression are recorded in adipose tissue, along with a disease exacerbation in mice fed with an HFD diet [4,182] (Table 3) Interestingly, adiponectin-knockout (APN-KO) mice present as more severe in comparison to WT mice [207][208][209]. Adenovirus-mediated supplementation of APN significantly attenuates the severity of colitis in both APN-KO and WT mice [207,210].…”
Section: Experimental Studies On Role Of Adipose Tissue In Ibdmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, leptin expression is elevated and adiponectin decreased in adipose tissue in rats with colitis fed with a normal diet, and this effect is markedly enhanced in rats fed with an HFD diet. This observation is further supported in studies in mice because the increased leptin and decreased adiponectin plasma levels and elevated expression of leptin and decreased adiponectin expression are recorded in adipose tissue, along with a disease exacerbation in mice fed with an HFD diet [4,182] (Table 3) Interestingly, adiponectin-knockout (APN-KO) mice present as more severe in comparison to WT mice [207][208][209]. Adenovirus-mediated supplementation of APN significantly attenuates the severity of colitis in both APN-KO and WT mice [207,210].…”
Section: Experimental Studies On Role Of Adipose Tissue In Ibdmentioning
confidence: 69%
“…Obeid et al [209] 2017 DSS-induced colitis in APN-KO mice APN-KO mice which have shown an aggravation of DSS-induced colitis have a greater inflammatory cell infiltration and higher presence of activated B cells in comparison to controls, accompanied by an elevated proinflammatory cytokine profile production.…”
Section: Year Study Type Conclusionmentioning
confidence: 99%
“…Administration of DSS for 6 consecutive days led to colitis as evidenced by body weight loss, diarrhea, shortening of the colon, and histopathological alterations, which was greatly ameliorated by Hyp. It has been reported that the overactivation of inflammatory response is a critical mediator associated with the onset of colitis . The concentrations of Hyp in the serum or colonic tissues were greater in Hyp supplementation and Hyp plus DSS co‐treatment groups as compared with that of controls.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, adiponectin-deficient mice exhibited more severe colitis, decreased intestinal epithelial proliferation, increased apoptosis and cellular stress when induced with dextran sulfate sodium (DSS). This colitis was reversed in vitro when adiponectin was present [100]. However, in vivo models have suggested conflicting results and require further study.…”
Section: Adipokinesmentioning
confidence: 97%